Eurocentrism in translation studies - Doorslaer, Luc van, 1964-; Flynn, Peter (Translator) (Benjamins current topics, 2013)
In his 2008 book, Translation and Identity in the Americas, Edwin Gentzler proposed a "fictional turn" to refer to translation in connection with the construction of identity in the Americas, a highly positive view of the role played by this activity since the arrival of the Europeans. This paper proposes a "fictionalizing twist," that is, a complementary approach that would attest to the less positive use of translation in the relation between Europe and the Americas on the one hand, and among European nations on the other. Thus, I examine how translation and Translation Studies have contribu.